Маскираната карневализација во „Слово за празниците“ на Кирил Пејчиновиќ - Tasevska Hadji Boshkova, Iskra (Филолошки факултет „Блаже Конески“, 2009)
Facing the contemporary challenges filled with explicit and imploded communication and information, we are inevitably interposed between constant extending of interpretative models, multiplied as well as various. That cognitive accumulation creates an additional quality, rendered as highly perspective. It is impossible to pass by this process, and that is the reason why we have to bring carnivalization up for discussion, mainly determined in Bakhtin’s theoretical sense, but also defined and generated into the 19th century Macedonian literature. The hypothesis of masked carnivalization that we laid down implies a spectra and intersection with constellation of interpretative strategies. Our goal is to give this text the place he deserves, according to the authentic and dominant element-subversive and transforming dialogism focused on dominant folk believes and customs, but also on simplistically accepted dogmatic and canons of Christian religion and ideology. Although this is not a classic representative of literary carnivalization, yet we are able to feel the anticipated ambivalence. It creates the necessary discontinuity of chronological sequence as important part of re-defining the discourse, wiping out tradition and mentality, thus enabling the divergent lines of individual utterances into the discursive field, and creating a resistance towards foisted social domination and historical continuity.